2016
DOI: 10.1002/hep.28459
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of operational tolerance with a regulatory T‐cell‐based cell therapy in living donor liver transplantation

Abstract: Potent immunosuppressive drugs have significantly improved early patient survival after liver transplantation (LT). However, long-term results remain unsatisfactory because of adverse events that are largely associated with lifelong immunosuppression. To solve this problem, different strategies have been undertaken to induce operational tolerance, for example, maintenance of normal graft function and histology without immunosuppressive therapy, but have achieved limited success. In this pilot study, we aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
326
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(334 citation statements)
references
References 47 publications
3
326
1
4
Order By: Relevance
“…Tregs have been proposed to be key in strategies aiming for tolerance and immunomodulation after SOT [35]. In a recent paper, Todo et al demonstrated that a single Treg injection might promote operational tolerance after living-related LT [36]. Recently, it has been demonstrated both in vitro and in vivo that MSCs could promote Treg expansion by their effects on immature dendritic cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Tregs have been proposed to be key in strategies aiming for tolerance and immunomodulation after SOT [35]. In a recent paper, Todo et al demonstrated that a single Treg injection might promote operational tolerance after living-related LT [36]. Recently, it has been demonstrated both in vitro and in vivo that MSCs could promote Treg expansion by their effects on immature dendritic cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Amazingly, Juntendo University, Tokyo, Japan and Hokkaido University, Hokkaido, Japan has succeeded in breaking away from immunosuppressive agents for human liver transplantation using ex vivo-generated regulatory T-cell-enriched cells 34) . After liver transplantations, 10 adult patients were given a novel regulatory T-cell-based cell therapy and have been drug free for 16-33 months since.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard promising results have been observed using tolerogenic islet antigens to inactivate effector T cells in animal models [124]. In Treg cell therapy, antigen specific Tregs produced by selective expansion in vitro has already been tested in liver transplantation and Crohn's disease [125,126]. The low frequency of islet antigen specific Tregs and the propensity of Tregs to destabilize after repeated in vitro stimulation makes selective expansion of islet antigen specific Tregs challenging.…”
Section: Discussionmentioning
confidence: 99%